El Excentrico, 1974-05-05 - Garcia, Humberto:::Publisher::::::::::::; Garcia, Bert:::Manager::::::::::::; Garcia, Marc:::Editor:::::::::::: (San Jose, California; Garcia Printing, 2023)
May 5, 1974 [5 de mayo de 1974]. No issue or volume number. Cover has a photograph of comedian Mario Moreno being presented with a plaque by Alberto Rodriguez, the former president of the Asociacion Nacional de Exhibidores de peliculas en español en Estados Unidos [the National Association of Spanish Language Motion Picture Exhibitors].